2017
DOI: 10.1371/journal.pone.0186643
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intrahepatic and extrahepatic cholangiocarcinoma in the United States: A population-based study in SEER-Medicare

Abstract: ObjectivesIntrahepatic (ICC) and extrahepatic (ECC) cholangiocarcinomas are rare tumors that arise from the epithelial cells of the bile ducts, and the etiology of both cancer types is poorly understood. Thus, we utilized the Surveillance, Epidemiology, and End Results (SEER)-Medicare resource to examine risk factors and novel preexisting medical conditions that may be associated with these cancer types.MethodsBetween 2000 and 2011, 2,092 ICC and 2,981 ECC cases and 323,615 controls were identified using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
202
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 166 publications
(209 citation statements)
references
References 49 publications
4
202
2
1
Order By: Relevance
“…As in previous studies, we found higher ICC incidence rates for males, Hispanics and other non‐Hispanic racial/ethnic groups, and older ages. ICC risk factors include chronic liver diseases and cirrhosis, biliary stones, infections (hepatitis B and C viruses and liver flukes), bile duct anomalies, some autoimmune diseases, obesity, diabetes, and smoking . Although the prevalence of these risk factors differs by demographic group, the commonality is that they involve inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…As in previous studies, we found higher ICC incidence rates for males, Hispanics and other non‐Hispanic racial/ethnic groups, and older ages. ICC risk factors include chronic liver diseases and cirrhosis, biliary stones, infections (hepatitis B and C viruses and liver flukes), bile duct anomalies, some autoimmune diseases, obesity, diabetes, and smoking . Although the prevalence of these risk factors differs by demographic group, the commonality is that they involve inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Some case reports and case series suggest an association between hemochromatosis and iCCA development . Results from the US SEER registry reported an OR = 2.07 (95% CI 1.33‐3.22) for iCCA, whereas no increased risk was found for eCCA . This last finding is not totally surprising, as iron deposition preferentially occurs in the liver.…”
Section: Risk Factorsmentioning
confidence: 95%
“…Both ulcerative colitis and Crohn's disease were found to be associated with increased CCA risk, although a stronger association was found for ulcerative colitis (RR = 3.40, 95% CI 2.50‐4.62 vs RR = 2.69, 95% CI 1.59‐4.55 respectively) . A recent analysis based on the US SEER registry also confirmed a stronger association with iCCA for ulcerative colitis (OR = 2.18, 95% CI 1.61‐2.95) compared to Crohn's disease (OR = 1.77, 95% CI 1.13‐2.75), whereas a similar increased risk was found for eCCA (OR = 1.75, 95% CI 1.32‐2.33 vs OR = 1.71, 95% CI 1.17‐2.51) . Both pathological conditions may be related to CCA development by induction of chronic inflammation and/or microbiome dysbiosis .…”
Section: Risk Factorsmentioning
confidence: 96%
“…This study utilized deidentified SEER‐Medicare data and therefore has been determined to meet criteria for exemption from IRB requirements by the NIH Office of Human Subjects Research Protections. The SEER database catalogs information on cancer cases reported in 18 regional registries across the United States, representing approximately 28% of the American population . Prospective data collection includes patient demographics and cancer‐specific information, including tumor histology, stage at diagnosis, treatment, and clinical outcomes.…”
Section: Methodsmentioning
confidence: 99%